Vienna Philharmonic, 4th subscription concert, December 16, 1900, conducted by Gustav Mahler - Wiener Philharmoniker:::Creator:::::::::::: (Vienna; Austria; Verlag der Philharmonischen Concert-Unternehmung, 2020)
Program/handbill for the Vienna Philharmonic concert on December 16, 1900 conducted by Gustav Mahler, in an all-Beethoven program including the Symphony no. 1, op. 21; the Coriolan Overture, op. 62, and the Symphony no. 4, op. 60.